Evolução e avaliação da Revista ACB: Biblioteconomia em Santa Catarina enquanto fonte de pesquisa (2000-2004) Evolution and evaliation of Revista ACB: Biblioteconomia em Santa Catarina as a research source (2000-2004) p. 5-7 - Bressane, Julia Miranda; Ohira, Maria Lourdes Blatt (Revista ACB, 2007)
Estudo do periódico Revista ACB: Biblioteconomia em Santa Catarina, editado pela Associação Catarinense de Bibliotecários. Visa o conhecimento da tendência da literatura utilizada pelos autores de artigos publicados na referida revista entre 2000 e 2004, e a comparação dos resultados deste período com os obtidos em estudo anterior, realizado com os fascículos da revista publicados entre 1996 e 1999. A análise dos dados é dividida em duas vertentes: a) análise de autoria, envolvendo número de autores, tipo de autoria, produtividade, titulação e vínculo institucional e b) análise de citação, que aborda aspectos como número de referências utilizadas, média de citações por artigo, tipologia dos documentos citados, idioma dos documentos, títulos de periódicos mais citados e autores mais citados. Abstract: Evaluates Revista ACB: Biblioteconomia em Santa Catarina magazine - published by the Librarians Association of Santa Catarina - whose objectives are the knowledge of literary tendency used by the authors of the articles published in the journal from 2000 to 2004, and the comparison of the current results with those reached in the first research, that has analyzed the magazine in the period of 1996 to 1999. The data analysis is divided into two segments: a) authorship analysis involving amount of authors, type of authorship, productivity, education level, and institutional affiliation; and b) citation analysis, which approach aspects such as amount of utilized references, average of citations in each article, typology of the cited documents, language used on this docs, and most cited scientific journals’ titles and authors. The evaluation is based on the author’s identification regarding the title, the origin institution and the number of written articles. The average of bibliographic citations used in each article, kinds of documents, its language, the identification of the greatest impact magazines and authors are also part of the study.